National Assembly Makes Laws or Suspends Laws - Dung, Nguyen Dang; Duong, Nguyen Thuy (VNU Journal of Science: Legal Studies, 2019)
Although there has not been a reform like executive and judicial power , since the “Doi Moi” reform until now, the National Assembly - the legislative branch of Vietnamese government has achieved certain successes, but to implement 2013 Constitution better, there ‘s still a lot of work to do. First of all, we have to change our awareness: Legislative power is not simply the right to adopt a law, but also the right to suspend law drafting when the laws do not express the will of the people, nor do they reflect objective movement of society. Keywords: National Assembly, legislative power, right to cease the making law.